IMPLEMENTASI PAJAK PENGHASILAN PASAL 21 PADA PT XYZ - Lia Ekowati; Agus Buntoro, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The purpose of this study is to analyze the implementation of Article 21 Income Tax, and the selection of Article 21 Income Tax calculation methods for permanent employees of PT XYZ. This type of research is qualitative research with a descriptive approach that explains or describes in detail a situation through data in the form of numbers. The data used are primary data and secondary data. Data collection techniques in this study used interviews, observation, documentation and literature studies. The results showed that PT XYZ's tax compliance was good, but the implementation of the calculation and withholding of Article 21 Income Tax for permanent employees was not in accordance with Law Number 36 of 2008 as amended by Law Number 7 of 2021. The calculation method of Article 21 Income Tax used by the company should be the Gross Up method which has a positive impact on employees and the company.